Comparative Analysis Of Stock Prices and Trading Volume of Pharmaceutical Companies Before and After The Covid-19 Pandemic (Case Study Of Companies Listed on The IDX 2018-2023) - Indri Kusuma Wardani (International Humanities and Applied Science Journal, 2026)
Global financial markets, particularly in Indonesia, were significantly affected by the COVID-19 pandemic, and the pharmaceutical sector attracted heightened investor attention during this period. This study compares stock prices and trading transaction volumes of pharmaceutical companies listed on the Indonesia Stock Exchange before and after the COVID-19 outbreak. Using a comparative quantitative approach with purposive sampling, seven firms were selected from a population of eleven over the 2018–2023 period. Because the data were not normally distributed, hypotheses were tested using the non-parametric Wilcoxon Signed Rank Test. The results indicate statistically significant differences in both stock prices and trading transaction volumes between the pre-pandemic and post-pandemic periods. Stock prices increased in the post-pandemic period, reflecting improved valuation of pharmaceutical firms during the crisis, while trading volume also changed significantly, indicating a shift in market participation and liquidity conditions. These findings suggest that the pandemic carried information content that reshaped investor behavior toward pharmaceutical stocks. This study contributes to understanding sectoral market dynamics during global health crises and provides insights for investors, regulators, and corporate managers regarding valuation and liquidity considerations. Keywords: Stock Price, Trading Transaction Volume, Covid-19, Wilcoxon Signed Rank Test